International conflicts in the mirror of constructive journalism: media geographical research - Tamara S. Yakova (RUDN Journal of Studies in Literature and Journalism)
Presents the results of the study of publications by influential global mass media about international conflicts from the standpoint of the concept of constructive journalism. Examines the dynamics of the transformation of media behavior of Internet audiences in different regions of the world in relation to the topics of international conflicts through the prism of media-geographical views on the processes of formation of media reality. The research methodology was based on the implementation of media metric analysis, rank analysis and content analysis in the context of constructive journalism. During the study, special attention was paid to the interpretation of meanings (substantially related to international conflicts) and spatial analysis of big data. The empirical basis of the study was Google Trends statistics and data obtained as a result of processing publications of influential global mass media devoted to international conflicts and crises, interest in which was shown by Internet audiences of countries of the world (the Arab-Israeli conflict, the conflict in Afghanistan, the US-Iran conflict, the Taiwan crisis). Content analysis of media texts confirmed the conclusion that the topic of international conflicts attracts the attention of Internet audiences and occupies a significant place on the agenda of influential global mass media, but only about 10% of materials published in 2023 meet the criteria for constructive journalism.